Everything Old Is New Again: A Comparison of Midcentury American EDP Schools and Contemporary Coding Bootcamps. - Miltner, Kate M. (Information & Culture, 2022)
Over the course of the past decade, coding has been positioned as a silver-bullet solution for several key issues in the US tech industry. The coding bootcamps that have sprung up in response to the contemporary coding obsession may appear innovative, but they bear a remarkable resemblance to the electronic data programming (EDP) schools that proliferated during the "software crisis" of the 1960s and 1970s. By comparing the current coding craze and coding bootcamps to the software crisis and EDP schools, this article not only draws attention to the remarkable similarities between the two periods and institutional forms but also identifies specific qualities and problematic practices of EDP schools that threaten to repeat themselves with coding bootcamps. It then concludes with some reflections about why certain "forgotten" histories of computing are more relevant now than ever.